PELATIHAN IMPLEMENTASI IoT PENGONTROL KUALITAS AIR BERBASIS WEB DI KOLAM IKAN MINA NGREMBOKO - Pramono, Dedi; Widyatama, Rendra; Aribowo, Eko; Saputra, Rendie Abdi (Jurnal Berdaya Mandiri, 2025)
This training aims to provide understanding and skills to partners of Mina Ngremboko fish farmers in Bokesan Hamlet, Sindumartani, Ngemplak, Sleman, Yogyakarta. The problem for fish farmer partners lies in the ineffectiveness of controlling pond water quality. So far, partners have used titen science, so the accuracy of water conditions cannot be properly known. This training is to introduce a water control device by implementing IoT (Internet of Things) that can control water acidity (pH): 6.5-8.5, dissolved oxygen conditions: 5mg/L, and water temperature: 20-30’C. This tool can operate automatically so that partners can know the condition of the pond water in real-time using the web. In this case, partners can check the water condition from their mobile phones or laptops anywhere. This training is beneficial as evidenced by the increased understanding of knowledge about IoT implementation through the results of the average pre-test score on a scale of 100 of 61.20 and the average post-test score of 85.83. This data shows an increase in understanding of 24.63 points. As for attitudes and skills towards IoT which are detailed in 3 (three) categories, namely (1) attitudes towards technological innovation, the results obtained are the percentage of partners who agree and strongly agree in the pre-test score of 88 and post-test 96, (2) perception of the benefits of technology, pre-test score 86 and post-test 95, and (3) perception of ease of use, pre-test score 86 and post-test 91. This shows that the attitudes and skills of Mina Ngremboko fish farmers have had quite high support for the application of technology from the start. Thus, this training proves that the implementation of IoT as a web-based water quality controller can be implemented optimally. Keywords: Web-based IoT, training, water quality controller, Mina Ngremboko